Employment Of Legend In The Very Short Hebrew Story - Alkhazali, Shaima Fadhil Hammoudi Ali (Al-Adab Journal, 2020)
Myth: It is a sacred story that includes the subject of creation and the beginning of existence and is defined as the work outside the familiar and extraordinary habits of human characteristics. It explains the secrets of life and the universe in a narrative style revolving around religious and social traditions and beliefs, and describes the exciting events that crystallized the process of creation and the role it played Various gods and mythical creatures in these events. And employing the legend is a process of mixing the past and the present, and when the ancient Hebrew literature had grown up in an environment in which the multiplicity of deities flourished and human figures appeared in it who rose to the level of divinity and attributed to him the works that are attributed only to the gods, the image of man emerged in many of the stories Legendary or semi-legendary, which carries some features outside the framework of humans, and thus modern Hebrew literature in its handling of the concept of conflict derives many legends and miraculous works that are mentioned in the stories of the Old Testament and in the myths of the ancient world as well and were mixed in literary works and crystallized with Subject to intellectual new, perhaps were not present in the original texts.